Hydropower Megaprojects in Colombia and the Influence of Local Communities: A View from Prospect Theory to Decision Making Process based on Expert Judgment used in Large Organizations - Garcia, Rodolfo; Zerda, Alvaro (International Journal of Energy Economics and Policy, 2016)
Today conflicts between large organizations that promote hydroelectric megaprojects (Sovacool, et al, 2015) and local communities are predictable (Ansar, et al., 2014). In literature, the causes of these levels of conflict are explored from the point of view of power relationship (Goodwin & Jasper, 1999) and stakeholder framework theory (Rosso, et al., 2014). This paper presents an original way to address this research field through an endogenous view (Mieg H. A., 2014) of the organizations focused on decision making process based on expert judgment. The study scopes are environmental decisions under uncertainty that are carried out to develop environmental impact assessment. All organizations that are developing large hydroelectric projects in Colombia during period 2010-2020 were examined. The results indicate the difficulty of organizations (Moritz & Gieri, 2015) to adequately respond to external requests associated with environmental and technological dimensions. Cumulative prospect theory and heuristic and biases framework (Brighton & Gigerenzer, 2015) are the theoretical background. Energy policy recommendations are generated based on adjustment type "external view" that comes from behavioral organizational framework (DellaVigna, 2009). This study identifies a novel approach to design lesser levels of conflict through creating better organizational decision making processes. Keywords: Decision making theory, large organizations, cumulative prospect theory, megaproject JEL Classifications: D22, Q51, L90